2017
DOI: 10.3390/ijgi6110340
|View full text |Cite
|
Sign up to set email alerts
|

Contributors’ Withdrawal from Online Collaborative Communities: The Case of OpenStreetMap

Abstract: Online collaborative communities are now ubiquitous. Identifying the nature of the events that drive contributors to withdraw from a project is of prime importance to ensure the sustainability of those communities. Previous studies used ad hoc criteria to identify withdrawn contributors, preventing comparisons between results and introducing interpretation biases. This paper compares different methods to identify withdrawn contributors, proposing a probabilistic approach. Withdrawals from the OpenStreetMap (OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…In another study (Bégin et al 2017b), we found that the rate at which VGI contributors withdraw from an online community depends on project's ability to fulfil contributors needs, desires or aspirations (Clary et al 1998, Penner 2002, Nov 2007, Budhathoki 2010, and the time it takes them to lose interest in the project. Factors such as required knowledge and skills, community norms and rules and other participants' behaviours may discourage most new contributors from pursuing their participation beyond the first few days.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In another study (Bégin et al 2017b), we found that the rate at which VGI contributors withdraw from an online community depends on project's ability to fulfil contributors needs, desires or aspirations (Clary et al 1998, Penner 2002, Nov 2007, Budhathoki 2010, and the time it takes them to lose interest in the project. Factors such as required knowledge and skills, community norms and rules and other participants' behaviours may discourage most new contributors from pursuing their participation beyond the first few days.…”
Section: Introductionmentioning
confidence: 89%
“…Factors such as required knowledge and skills, community norms and rules and other participants' behaviours may discourage most new contributors from pursuing their participation beyond the first few days. The same study (Bégin et al 2017b) proposed three overarching stages in the life cycle of contributors adapted from the life cycle of complex systems in reliability engineering (Wang et al 2002). First, an 'assessment' stage (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study estimated that only 64% of new OSM contributors "survive" their first day, after which the estimated survival rate decreases [9], suggesting that the 50% withdrawal rate observed in [8] is not specific to mapping parties. Apart from mapping parties, OSM shows other characteristics of a social project.…”
Section: Introductionmentioning
confidence: 99%
“…Mapping parties and mapathons help generate data, but most mappers appear to be unlikely to continue mapping on their own, even if they may be motivated to pursue mapping [7,19]. In a study of contributors' withdrawal from OSM, Bégin, Devillers, & Roche [20] discovered that a large majority of participants withdraw during a short "assessment" phase in which contributors explored the project to determine if they would engage in the long term.…”
Section: Related Workmentioning
confidence: 99%